Numerical study on the cyclic behavior of the stiffened steel plate shear walls containing sandwich panels with corrugated core - Shuna Zhang; Peng Zhang; Shaopeng Wang; Amir Ghiasvand (Scientific Reports)
Abstract Steel Shear Walls (SSWs) are known as structures that dampen the seismic loads like earthquakes in every construction, especially in tall buildings. The SSW contains three critical elements; beam, column, and infill plate. These elements have a significant effect on the seismic performance of the SSWs. The infill plate of SSW is important due to the absorption of the induced external energies. The current research paper studied different configurations of the sandwich panels with trapezoidal corrugated cores as the stiffeners inside the infill plate of the SSWs numerically in the presence of cyclic loading conditions. Two directions the horizontal and vertical are considered for the stiffeners. Also, various numbers of rows and columns are assumed for the stiffeners. The initial model was validated with the published experimental data. According to the average values that obtained, the horizontally and vertically oriented sandwich panels increase the plastic dissipation energy of the SSWs by around 156% and 196%, respectively. The outputs derived from this study will help to increase the SSWs’ strength in the built constructions by using sandwich panels inside them. Because the sandwich panels have low weight and high strength compared to the other stiffening systems.